Antibacterial antivities of protein extracts from Andrographis paniculata, Tinospora crispa and Centella asiatica - Md Zin, Noor Hasniza; Ahmad, Nurul Fatihah; Mohammad Bunnori, Noraslinda; Abdul Wahab, Widya; Haron, Normah (2016)
Andrographis paniculata, Tinospora crispa and Centella asiatica are known to have various pharmacological functions. This research was carried out to investigate the antibacterial activities of protein extracts from Andrographis paniculata, Tinospora crispa and Centella asiatica